Tanggung Gugat Pejabat Pembuat Akta Tanah terhadap Karyawan yang Melakukan Tindak Pidana Penggelapan - Frieskythasari, Nadya; Laila, Fathul (Universitas Negeri Malang, 2021)
This study aimed to analyze the liability of land deed officials in Decision Number 179/Pid.B/2015/PN.Sungguminasa and legal protection for land deed officials for criminal acts of embezzlement committed by employees. The method used in this study was normative juridical with a case approach and a statutory approach. The accountability of the land deed official in Decision Number 179/Pid.B/2015/PN.Sungguminasa related to the criminal act of embezzlement by his employees was completed in an authentic deed belonging to the aggrieved appeared by bearing all the administrative costs. Legal protection for land deed officials for criminal acts of embezzlement committed by their employees was categorized in preventive and repressive legal protections. Preventive legal protection was guided by Article 55 paragraph (1) of the Criminal Code, which stated that a crime could be given to a party who commits, orders, and participates in committing a crime. Repressive legal protection was guided by Article 50 paragraph (1) of the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 2 of 2018, which stated that ministries, assemblies, or organizations of the Association of Land Deed Makers might provide legal assistance to land deed officials whom investigators summon.